Factors associated with the prevalence of induced Abortions among Females of age 16 to 30 years at Busiu Center IV, Mbale District. A Cross-sectional Study. - Wanale , Joshua (Student's Journal of Health Research Africa, 2022)
Background: Induced abortion is defined as a procedure done to end pregnancy [ACOG], and most induced abortions are done in the first 12 weeks of pregnancy. Methodology: The study was cross-sectional in design. This is so because it yields results in a short time. A simple random sampling technique was used to select 60 respondents who participated in the study. Results: The majority 35(58%) of the respondents were Bagisu and the least 4(7%) were Bagwere. Most 33(55%) of the respondents had attained secondary 12(40%) of the respondents had attained primary level, 9(15%) attained tertiary level and the least 6(10%) had attained none. The majority (43)72% of the respondents were in the age range of 16-26 years due to fact that this is the reproductive age group, still attending school, more sexually active, and are exposed to sexual and reproduction information and articles; of which most are not married having fear to sustain pregnancy and the least (17) 28% were 30-44 years as most of them are married thus with no fear for sustaining the pregnancy once they conceived. Conclusion: The study showed that most women of reproductive age had some knowledge of induced abortion but a few knew about safe induced abortion and the majority knew at least one method of induced abortion. Recommendations: This study highlighted the need for policymakers and health administrators to implement measures that would increase the knowledge of people on safe induced abortion including legal rights.